2019
DOI: 10.1186/s12888-019-2208-2
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa, eating patterns and personality traits: a cross-cultural comparison of Italian, Polish and Spanish university students

Abstract: Background The amount of research about orthorexic attitudes and behaviours has increased in the last five years, but is still mainly based on descriptive and anecdotal data, yielding a variety of prevalence data and inconsistent results. The interplay between socio-cultural context and orthorexia has been poorly investigated and is still far from being understood. Method Multicentre, cross-sectional study involving Italian ( N = 216), Polish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 49 publications
10
54
3
4
Order By: Relevance
“…In our study, it was found that almost half of the people with the ON tendency also displayed ED symptoms. The relationship between the ON tendency and ED symptoms is complex and not clear enough and hence needs to be studied in detail [36]. In some studies, ON was indicated as a predictor of ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, it was found that almost half of the people with the ON tendency also displayed ED symptoms. The relationship between the ON tendency and ED symptoms is complex and not clear enough and hence needs to be studied in detail [36]. In some studies, ON was indicated as a predictor of ED.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing ON tendency was five-fold higher in ED patients compared to healthy people [37]. Although ON tendency may precede ED, it may also occur during the remission phase of ED [36]. While some researchers consider ED as a risk factor for ON tendency [8], ED is also pointed out as a negative predictor of ON [38].…”
Section: Discussionmentioning
confidence: 99%
“…In each logistic regression model, the use of dietary supplements was the dependent variable, and ON was the independent variable. The variables identified as significant in the literature 10,12,13,26,31 and those found statistically significant in the univariate analysis (age, sex, the monthly income level of the family, perceived health status, number of main meals, BMI) were included as covariates in the models. Adjusted odds ratios were given at 95% confidence intervals.…”
Section: Orthorexia Nervosa Scalementioning
confidence: 99%
“…25 Indeed, in a limited number of studies in recent years, it has been reported that the rate of dietary supplement use is high in those with ON symptoms. 14,19,22,26 Turkish literature on the relation between ON and the use of dietary supplements is scarce. Our hypothesis is that the use of dietary supplements in nursing students is related to ON.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made based on BOT, by Donini and colleagues who developed "ORTO-15," a designed instrument to detect ON [9,14]. Donini and colleagues were expanded the scoring to a 1 to 4 scale (always, often, sometimes, never) regarding dietary habits food preference, where the scores range between 15 as a minimum score and 60 as a maximum score [15]. However, lower scores indicate more extreme dieting practices [9].…”
Section: Introductionmentioning
confidence: 99%